2020
DOI: 10.7759/cureus.11311
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Opioid Use Disorder and Social Determinants of Health: A Nationwide Analysis of the National Inpatient Sample (2012-2014 and 2016-2017)

Abstract: To evaluate the trends and relationship of inpatient presentations of Social Determinant of Health (SDOH) with superimposed Opioid Use Disorder (OUD), comparing 2012-2014 (ICD-9) and 2016-2017(ICD-10). MethodsWe used the Nationwide Inpatient Sample (NIS) from the Healthcare Cost and Utilization Project (HCUP). We identified OUD among patients with any record of SDOH as the primary or secondary diagnosis using the International Classification of Diseases (ICD)-9/10 codes. A weighted SDOH sample size of 3,002,55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Intoxicated patients also demanded greater hospital resources to facilitate care. Opioid‐intoxicated patients had greater odds of a prolonged LoS, which in the absence of more severe injury, may reflect required complex discharge planning, as well as challenges in managing acute pain in this population 21,22 . Despite no difference in ISS, we observed an increase in odds of requiring ICU admission among all intoxication groups, consistent with previously published literature 23–25 .…”
Section: Discussionsupporting
confidence: 86%
“…Intoxicated patients also demanded greater hospital resources to facilitate care. Opioid‐intoxicated patients had greater odds of a prolonged LoS, which in the absence of more severe injury, may reflect required complex discharge planning, as well as challenges in managing acute pain in this population 21,22 . Despite no difference in ISS, we observed an increase in odds of requiring ICU admission among all intoxication groups, consistent with previously published literature 23–25 .…”
Section: Discussionsupporting
confidence: 86%
“…The rate of presentation, as shown in this study, is about 1,205 per 100,000 births annually. High presentation rates were associated with socioeconomic and demographic indicators as shown by other studies [ 11 , 19 ].…”
Section: Discussionsupporting
confidence: 63%
“…Studies have found associations between unemployment, homelessness, drug use, and poor mental health in diverse communities. Family relationships and support are also important to consider as adolescents and young adults are likely to be influenced by behaviors they observe or perceive as acceptable based on childhood experiences (82). Interestingly, it has been proposed that internet access, dependent on place of residence, is another important SDOH to consider (81).…”
Section: Discussion Real World Importance Of Sdoh Datamentioning
confidence: 99%